Bem-estar subjetivo: aspectos conceituais - Luiza Santos Moreira da Costa (Arquivos Brasileiros de Psicologia, 2014)
It can be depicted from the analyses of publications in the topic Subjective Well-Being (SWB), that SWB/happiness is perceived as: a) trait; b) state; or c) "being in charge of his/her own life", according to different groups of authors. The concepts described on items a and b consider SWB composed by three components: satisfaction, positive affect and negative affect, which are also presented here. The concepts described in this paper can be used alone or combined, according to the researchers proposals. SWB is a valuable guidance and may be used on several areas of research.